Meningkatkan Pengetahuan dan Kesadaran Masyarakat Tentang Pentingnya Perilaku Hidup sehat dan pengelolaan sampah Di Kelurahan Sukarasa, Kota Bandung - iqbal; Kahar, Kahar; Kamaludin, Ade (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2024)
A healthy community is a key indicator of a quality and sustainable environment, which is achieved through healthy living behaviors and effective waste management. In Sukasari Village, structured community service efforts are needed by lecturers majoring in Environmental Health to increase community knowledge and awareness about the importance of these two aspects, in order to overcome challenges related to health and waste management that are still high. The method of service implementation begins with a situation analysis and needs identification in Sukasari Village through surveys and interviews, then educational materials on healthy living behavior and waste management are developed and delivered through training, workshops, and practical demonstrations. This program involves the formation of working groups at the RT/RW level for implementation and monitoring, ongoing campaigns, and ends with a comprehensive evaluation to measure behavior change and provide follow-up recommendations, with the hope of creating a cleaner and healthier environment. The community service program in Kelurahan Sukarasa succeeded in significantly improving knowledge, awareness, and practices related to healthy living behavior and waste management, with personal hygiene knowledge rising from 45% to 85% and waste management awareness rising from 30% to 80%. This success highlights the importance of continuing education and community-based approaches in addressing health and environmental issues, which overall help to reduce environmental burdens and improve community well-being. Communities are advised to continue developing and implementing sustainable education programs and participatory approaches to maintain and improve awareness and practices of healthy living and waste management in the community.